STUDI KARAKTERISTIK PERTUMBUHAN DAN PEMBUNGAAN Hippeastrum hybridum hort. cv. ”Red Lion” PADA TANGGAL TANAM YANG BERBEDA - Hanum, Siti Fatimah (Buletin Udayana Mengabdi, 2012)
Study on growth and flowering characteristic at different planting date done to gain optimum planting date of Hippeastrum hybridum hort.cv.’Red Lion’ at Bali Botanical garden nursery. In this research, three different planting dates, namely July 30, August 30, and September 30 were used. Parameter observed at this experiment was days to first leaf emergence, number of leaves, plant height, Days to flower scape emergence and number of bulblets per plants to know growing character. Number of flowers per scape, diameter of flower, and percent of flowering used to know flower character. It was observed that August planting gives the best result for number of flower per scape, plant height, number of leaves per plants and diameter of flower following by July planting. Late planting meaning September planting did not come out with satisfactory results.